Figure d'Atene nelle opere di Plutarco - Casanova, Angelo Alfredo (Firenze University Press, 2013)
The volume contains the text of nineteen contributions, elaborated by professors of eight European universities, linked together in the "Réseau Thématique Plutarque" (Madrid, Málaga, Coimbra, Paris X, Leuven, Groningen, Salerno, Florence) and intends to comment on the news provided from Plutarch on the life and activities, the importance and influence of the great figures of ancient Athens. Relevant contributions are proposed on famous political figures (Teseo, Solone, Pericle and Cimone); on the great Athenian philosophers (in particular Socrates, the tradition of the Platonic Academy and of the Peripate); on the astrologer Metone and Epimenide, the purifier of Athens; but also on famous women (in particular, Aspasia). Two chapters deal with the historical situation of Athens at the time of the Diadochi and in the Roman age. Two other chapters deal with the reception of two specific plutarchic works during the Renaissance: Gloria degli Ateniesi (Glory of Athenians) e Detti degli Ateniesi (Sayings of the Athenians).